2008
DOI: 10.1002/ijc.23486
|View full text |Cite
|
Sign up to set email alerts
|

Fetal growth and the risk of childhood CNS tumors and lymphomas in Western Australia

Abstract: The etiology of childhood cancers is largely unknown, although the early age at diagnosis has led to particular interest in in utero and perinatal factors. Birth weight is the most frequently studied perinatal factor in relation to risk of childhood cancers, and results have been inconsistent. We investigated whether the risk of CNS tumors and lymphomas in children was associated with three measures of the appropriateness of intra-uterine growth: proportion of optimal birth weight (POBW), birth length (POBL) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 43 publications
3
36
1
2
Order By: Relevance
“…An Australian study on fetal growth and risk of childhood CNS tumors found little evidence of an overall association, using relatively novel measures of fetal growth (proportion of optimal birth weight, length, and weight for length). 23 In contrast, a Nordic study (using part of the current data set) found a U-shaped relation between birth weight and CNS tumors.…”
Section: Figures 1 and 2 Andcontrasting
confidence: 63%
See 1 more Smart Citation
“…An Australian study on fetal growth and risk of childhood CNS tumors found little evidence of an overall association, using relatively novel measures of fetal growth (proportion of optimal birth weight, length, and weight for length). 23 In contrast, a Nordic study (using part of the current data set) found a U-shaped relation between birth weight and CNS tumors.…”
Section: Figures 1 and 2 Andcontrasting
confidence: 63%
“…22,23 A 2012 meta-analysis, encompassing 2 cohort and 7 case-control studies, found no statistically significant associations between birth weight and lymphoma in general or between birth weight and major lymphoma categories (non-Hodgkin' s and Hodgkin' s lymphoma). 5 A national Swedish cohort study, overlapping partly with the Swedish data in our study, reported that increased fetal growth was associated with non-Hodgkin' s lymphoma in early life, independent of gestational age and other perinatal factors.…”
Section: Figures 1 and 2 Andmentioning
confidence: 99%
“…We previously reported an increased risk of ALL (acute lymphocytic leukaemia) (Milne et al, 2007), of Hodgkin lymphoma and Burkitt lymphoma among boys, and of non-Hodgkin lymphoma among girls (Milne et al, 2008) in association with increasing proportion of optimal birth weight, a measure of the appropriateness of fetal growth (Blair et al, 2005). These findings are consistent with a biologically plausible mechanism of accelerated growth associated with growth factors in normal as well as cancer cells.…”
supporting
confidence: 66%
“…As in our approach with childhood ALL (Milne et al, 2007), CNS tumors and lymphomas (Milne et al, 2008), we aimed to distinguish an effect of high birth weight per se and one with accelerated growth. We restricted the univariate regression analysis of POBW to, in turn, children with birth weights below two commonly used definitions of high birth weight: 43500 and 44000 g. The positive associations observed between POBW and retinoblastoma and rhabdomyosarcoma were also observed among children with birth weights o3500 and o4000 g: retinoblastoma (HR: 1.39, 95% CI 0.82 -2.36 and HR: 1.32, 95% CI 0.89 -1.95, respectively); and rhabdomyosarcoma (HR: 1.53, 95% CI 0.82 -2.86 and HR: 1.55, 95% CI 1.00 -2.40, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation